Jen wants to tile the floor of her kitchen . The floor is recrangular and measures 12 feet by 8 feet. If it costs $2.50 per square foot for the materials, what is the total cost of the materials, what is the total cost of the materials for tiling the kitchen floor?

Answers

Answer 1
Answer: Given:
rectangular floor
length = 12 feet 
width = 8 feet

Area = 12 ft * 8 ft = 96 ft²

Cost of $2.50 per square foot

96 ft² * $2.50 = $240

The total cost of the materials for tiling the kitchen floor is $240.
Answer 2
Answer:

we know that

The area of the floor of the kitchen is equal to the area of a rectangle

so

Step 1

Find the area of the kitchen

we have

A=12*8\n A=96 ft^(2)

Step 2

Find the cost

we know that

the cost is $2.50 per square foot

so

by proportion

(2.50)/(1) =(x)/(96) \n\n x= 2.50*96\n x=240

therefore

the answer is

the total cost of the materials for tiling the kitchen floor is $240


Related Questions

A pyramid has cross-sectional, taken parallel to its base that are?
Joel opened a checking account. His bank charges him a service fee of $4.95each month. Assume y = total cost of having the account and x = number of months.
2. What is the area of a square computer screen with 21-in. sides? A. 220 sq. in. B. 42 sq. in. C. 441 sq. in. D. 84 sq. in
The number( √5 +2)(√5 - 2) is a. an irrational number b. a rational number c. not a natural number d. none of these
The currency in Brazil is called the Brazilian real and is represented by R$. A Brazilian real is similar to the US dollar in that R$1 is divided into 100 parts, called centavos.Fatima lives in Michigan and is traveling to Brazil. She knows R$1 = $0.32 (US). How many Brazilian real will she receive when she exchanges $750 (US)?

Please help me with angles.

Answers

Answer:

Step-by-step explanation:

Solve the system of equations by finding the reduced row-echelon form of the augmented matrix for the system of equations.

Answers

Answer:

Option (a) is correct.

The solution is (1, -1 , -4)

Step-by-step explanation:

Given:

A system of equation having 3 equations,

2x+y+z=-3\n\n 3x-5y+3z=-4\n\n 5x-y+2z=-2

We have to solve the system of equations by finding the reduced row-echelon form of the augmented matrix for the system of equations.  

 Consider  the given system

2x+y+z=-3\n\n 3x-5y+3z=-4\n\n 5x-y+2z=-2

Write in matrix form as

\begin{pmatrix}2&1&1\n \:3&-5&3\n \:5&-1&2\end{pmatrix}\begin{pmatrix}x\n \:y\n \:z\end{pmatrix}=\begin{pmatrix}-3\n \:-4\n \:-2\end{pmatrix}

⇒  AX = b

Writing in Augmented matrix form , [A | b]

\begin{pmatrix}2&1&1&-3\n 3&-5&3&-4\n 5&-1&2&-2\end{pmatrix}

Apply row operations to make A an identity  matrix.

R_1\:\leftrightarrow \:R_3

=\begin{pmatrix}5&-1&2&-2\n 3&-5&3&-4\n 2&1&1&-3\end{pmatrix}

R_2\:\leftarrow \:R_2-(3)/(5)\cdot \:R_1

=\begin{pmatrix}5&-1&2&-2\n 0&-(22)/(5)&(9)/(5)&-(14)/(5)\n 2&1&1&-3\end{pmatrix}

R_3\:\leftarrow \:R_3-(2)/(5)\cdot \:R_1

=\begin{pmatrix}5&-1&2&-2\n 0&-(22)/(5)&(9)/(5)&-(14)/(5)\n 0&(7)/(5)&(1)/(5)&-(11)/(5)\end{pmatrix}

R_3\:\leftarrow \:R_3+(7)/(22)\cdot \:R_2

=\begin{pmatrix}5&-1&2&-2\n 0&-(22)/(5)&(9)/(5)&-(14)/(5)\n 0&0&(17)/(22)&-(34)/(11)\end{pmatrix}

R_3\:\leftarrow (22)/(17)\cdot \:R_3

=\begin{pmatrix}5&-1&2&-2\n 0&-(22)/(5)&(9)/(5)&-(14)/(5)\n 0&0&1&-4\end{pmatrix}

R_2\:\leftarrow \:R_2-(9)/(5)\cdot \:R_3

=\begin{pmatrix}5&-1&2&-2\n 0&-(22)/(5)&0&(22)/(5)\n 0&0&1&-4\end{pmatrix}

R_1\:\leftarrow \:R_1-2\cdot \:R_3

=\begin{pmatrix}5&-1&0&6\n 0&-(22)/(5)&0&(22)/(5)\n 0&0&1&-4\end{pmatrix}

R_2\:\leftarrow \:-(5)/(22)\cdot \:R_2

=\begin{pmatrix}5&-1&0&6\n 0&1&0&-1\n 0&0&1&-4\end{pmatrix}

R_1\:\leftarrow \:R_1+1\cdot \:R_2

=\begin{pmatrix}5&0&0&5\n 0&1&0&-1\n 0&0&1&-4\end{pmatrix}

R_1\:\leftarrow (1)/(5)\cdot \:R_1

=\begin{pmatrix}1&0&0&1\n 0&1&0&-1\n 0&0&1&-4\end{pmatrix}

Thus, We obtained an identity matrix

Thus, The solution is (1, -1 , -4)

This  involves quite a lot of arithmetic to do manually.

The first thing you do is to make the first number in  row 2  = to 0.

This is done by R2 = -3/2 R1 + R2

so the matrix becomes

( 2        1          1)    ( -3 )

( 0    -13/2   3/2)   (1/2 )

(5       -1           2)  (-2)

Next step is to make  the 5 in row 5  = 0  

then  the -1  must become zero

You aim  for the form

( 1 0 0) (x)

(0 1 0) (y)

(0 0 1) ( z)

x , y and z will be the required solutions.


Find two whole numbers whose sum is 60 and whose difference is 12

Answers

\left \{ {\big{x+y=60} \atop \big{x-y=12}} \right. \n--------\nx+x=60+12\n2x=72\ /:2\nx=36\n\nx+y=60\ \ \ \Rightarrow\ \ \ y=60-x\ \ \ \Rightarrow\ \ \ y=60-36=24\n\nAns.\ the\ numbers:\ 36\ \ and\ \ 24

Can someone help me with this problem?

Answers

Hello,

W: math homework reulary

A: B average or better

U:Univers 100%

W∩A= the answer
Or #(W∪A)+#(W∩A)=#W+#A
or #(W∪A)=100-40=60

==>60+x=48+55
==>x=43

Find the value of x so that the function has the given value
f(x) = 4x -3; f(x) = 33

Answers

Answer:

x = 9

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

Algebra I

  • Function Notation

Step-by-step explanation:

Step 1: Define

f(x) = 4x - 3

f(x) = 33

Step 2: Solve for x

  1. Substitute:                    33 = 4x - 3
  2. Isolate x term:               36 = 4x
  3. Isolate x:                       9 = x
  4. Rewrite:                        x = 9

Which equation shows the substitution method being used to solve the system of linear equations? x – y = 7

x = y + 3


A) x = (7 – x) + 3

B) x – (y + 3) = 7

C) (y + 3) – y = 7

D) x – y = y + 3

Answers

I think it is answer C
Hope I helped